How do Mindfulness integrate Cognitive Behaviour Therapy Improves Mental Distress? An Evidence-Based Review - Mani, Santwana; Som, Rajashree Roy (International Journal of Psychosocial Rehabilitation, 2020)
--Research on the effects of mindfulness training have shown improvements in attention skills; social skills; sleep quality; well-being; and reductions in anxiety, depression, somatic, and externalizing symptoms in clinic-referred individuals. MiCBT is an integrated therapy of traditional establishment of mindfulness (Burmese Vipassana tradition of Ledi Sayadaw and U Ba Khin) with solid and deep-rooted principles of cognitive and behavioral traditions (CBT),developed by Dr. Bruno Cayoun. The aim of this study is to map, and assess the effectiveness of MiCBT on symptoms (Depression, Anxiety, Stress and OCD) of mental distress by analyzing randomized controlled design or quasi-experimental or pre-test/post-test design or within subject design. Systematic searches were conducted on electronic databases such as SCOPUS, Web of Science, Google Scholar, and PubMed for the time periods of 2010 to 2020. The 13 articles were screened but due to the inclusion and exclusion criteria only 8 articles were reviewed in the study. As the result found that MiCBT is effectual and comprehensive therapy treatment in reducing depression, anxiety, sleep quality, fatigue and stress for patients with MS (Pouyanfard., et al.2018;Bahrani.,et al.2017); efficacious in treating patients with POs without prominent overt compulsions (Kumar,A.,et al.2016); significant positive effects on mindfulness, flow, and pessimism(Hamilton et al.2016).However, in both clinical and non clinical population are being undertaken in view to study the efficacy of MiCBT, there is lack of empirical studies and to prove the efficacy of the therapy thoroughly, more experimental & RCTs are in need.